Islam Hadhari : the quest of commerce and trades / Husniyati Ali, 'Ismah Osman and Emi Normalina Omar - Ali, Husniyati; Osman, 'Ismah; Omar, Emi Normalina (UPENA, 2005)
The ethical values that have been stressed in the concept of Islam Hadhari are seen to be a motivating factor for man to work harder, have a sense of respect, self-discipline, honesty, justice, fairness and accountability, in order to ensure that the country would prosper and develop, as in line with the teachings of Islam. As far as trade and commerce is concerned, al-Qur'an has indeed pointed out that trade and commerce is made permissible in order to develop human being so that they will not suffer in poverty and difficulties. In Surah al-Baqarah verse 275 Allah SWT says: "But Allah hath permitted trade and forbidden usury..." Hence in the quest of trade man needs to adhere to the Islamic principles where the concept of lawfulness should be considered in the business activities. Whatever is permitted should be followed and whatever is forbidden should be restrained. This paper will discuss on some of quranic verses in terms of promoting economic growth and social development of the Muslim, and the nation, as a whole. Secondly, it will also highlight the challenges that the nation face in advocating development and growth in commerce and trades in Malaysia. Lastly, this paper will discuss on the approaches towards facing the competitive world of trade and commerce, caused by globalization and technological revolution. Consequently, Islam Hadhari could only be achieved, when the people only adhere to the principles and the regulations that have been underlined by Allah.